Revisión de los miliarios del tramo Caelionicco-Ad Lippos de la via XXIV del itinerario de Antonino (Calzada de la Plata) (Minerva. Revista de Filología Clásica, 2019)
This paper tries to do a wide statement and a complete picture of the epigraphy of the section Caelionicco-Ad Lippos from the Antonini Itinerarium's Way XXIV. This section of the itinerary offers an unusual and supplementary amount of milestones, whose information about the distance in miles to Emerita Augusta, caput viae of the itinerary, sometimes does not agree with reality. The author has collected and compared all the pieces found at this section of the Calzada de la Plata. Afterwards he has examined every piece and revised every inscription. Moreover the author has found two unpublished pieces, in very bad conditions, that increase the remarkable number of milestones from that Way.